ANALISIS PENGELOLAAN KEUANGAN RURAL INFRASTUCTURE SUPPORT PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (RIS–PNPM) DI ORGANISASI MASYARAKAT SETEMPAT (OMS) KECAMATAN TUAH NEGERI KABUPATEN MUSI RAWAS - YUNITA HASRINA (Program Studi Magister Manajemen FE Unsri, 2015)
This study aims to identify and analyze Financial Management Rural Infrastructure Support National Community Empowerment Program ( RIS - PNPM ) in Local Community Organizations (CSOs) sub-district of Musi Rawas Tuah State. The variables used in this study is financial management. The analytic technique used in this research is descriptive qualitative analysis. Based on the survey results revealed that the financial management of Rural Infrastructure Support National Community Empowerment Program ( RIS - PNPM ) in Local Community Organizations ( CSOs ) sub-district of Musi Rawas Tuah State has gone well, it is known to have responsibility, the ability to organize and manage finances, managed honestly, has the power effectiveness and efficiency, and effectively implemented in accordance with the available budget. Administrators and managers must have a human resource activities and have a good knowledge and mental activity that can be run either by giving pelatiahan - financial management training